Research into the quality of fuels and their biocomponents - Matijošius, Jonas; Sokolovskij, Edgar (Transport, 2009)
The article provides a closer look into the quality properties of fuels, analyses the merits and demerits of using biocomponents in petrol and diesel and overviews the ways of improving the quality of fuels. Work carried out by the authors covers the determination of the basic quality properties (density, kinematic viscosity and flash point) of petrol, diesel, methanol, ethanol, buthanol as well as rape methyl and rape ethyl esters. The paper investigates how these qualities influence the operational performance of the engine and puts forward the age‐dependence analysis of diesel quality properties.First published online: 27 Oct 2010